KOMUNIKASI PELAYANAN YANG EFEKTIF DENGAN PENGGUNAAN APLIKASI SMART DAN SAMAGOV: KELURAHAN SIDOMULYO, KECAMATAN SAMARINDA ILIR - Sy. Nurul Syobah; A. Rivai Beta; Vernalita Anata Dharmayanti; Siti Hajayana; Siti Nikmah Lana; Sodya An Nuryazza (Saweu: Jurnal Pengabdian Kepada Masyarakat, 2025)
The digitalization of services at the neighborhood (RT) level has become an essential instrument for accelerating public administrative services and strengthening communication between village officials and the community. This community engagement activity evaluates the effectiveness of service communication through the utilization of the SMART and SAMAGOV applications in RTs across Sidomulyo Subdistrict. The activity was conducted during the Sidomulyo Coordination Meeting (26 November 2025), involving RT heads, the LPM chairman, the TP PKK chairwoman, Babinsa, Bhabinkamtibmas, and the management of the Merah Putih Cooperative. The method employed was descriptive qualitative combined with Participatory Action Research (PAR) through field observations, meeting documentation, and semi-structured interviews. The results indicate improvements in information delivery speed, service transparency, and ease of citizen reporting; RTs play an essential role as digital mediators. The main challenges include residents’ varying levels of digital literacy, the need for continuous assistance, and limited internet access in certain areas. Recommendations include tiered digital literacy training, simple instructional modules, strengthened RT–Kelurahan helpdesk mechanisms, and coordinated efforts to enhance network infrastructure.